Catastrophic mitral prosthesis dehiscence diagnosed by three‐dimensional transesophageal echocardiography. Issue 4 (2nd August 2013) - Ciobanu, Andrea O.; Griffin, Steven C.; Bennett, Sean; Vinereanu, Dragos
ABSTRACT In emergency situations, real‐time three‐dimensional transesophageal echocardiography (RT 3‐dimensional TEE) may provide unique anatomic insights on prosthetic valves when two‐dimensional imaging is inconclusive. We report the case of a 76‐year‐old woman, in cardiogenic shock, who had undergone mitral valve replacement 3 months ago. RT 3‐dimensional TEE revealed almost total, catastrophic prosthesis dehiscence following infective endocarditis, the prosthesis being perpendicular to the normal mitral plane. Corrective surgery was not feasible, and the patient died shortly after admission. Although the outcome was unfortunate, RT 3‐dimensional TEE helped rapidly reach a definitive diagnosis, essential for decision‐making. Three‐dimensional TEE should be used as a complementary technique in difficult cases. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound 42:249–251, 2014